’We weren't checked in on, nobody spoke to us’: an exploratory qualitative analysis of two focus groups on the concerns of ethnic minority NHS staff during COVID-19 - Richard A Powell; Jehanita Jesuthasan; Victoria Burmester (BMJ Open)
Objective To gain exploratory insights into the multifaceted, lived experience impact of COVID-19 on a small sample of ethnic minority healthcare staff to cocreate a module of questions for follow-up online surveys on the well-being of healthcare staff during the pandemic.Design A cross-sectional design using two online focus groups among ethnic minority healthcare workers who worked in care or supportive roles in a hospital, community health or primary care setting for at least 12 months.Participants Thirteen healthcare workers (11 female) aged 26–62 years from diverse ethnic minority backgrounds, 11 working in clinical roles.Results Five primary thematic domains emerged: (1) viral vulnerability, centring around perceived individual risk and vulnerability perceptions; (2) risk assessment, comprising pressures to comply, perception of a tick-box exercise and issues with risk and resource stratification; (3) interpersonal relations in the workplace, highlighting deficient consultation of ethnic minority staff, cultural insensitivity, need for support and collegiate judgement; (4) lived experience of racial inequality, consisting of job insecurity and the exacerbation of systemic racism and its emotional burden; (5) community attitudes, including public prejudice and judgement, and patient appreciation.Conclusions Our novel study has shown ethnic minority National Health Service (NHS) staff have experienced COVID-19 in a complex, multidimensional manner. Future research with a larger sample should further examine the complexity of these experiences and should enumerate the extent to which these varied thematic experiences are shared among ethnic minority NHS workers so that more empathetic and supportive management and related occupational practices can be instituted.